Alternatives of reusing textile waste (Research, Society and Development, 2020)
Textile products are indispensable in everyday life, being present in different formats and characteristics. However, the textile industry is the second largest pollutant in the world due to the few of reuse and recycling techniques that cause great environmental impacts. Data show the recycling of textile waste does not reach 25% of what is generated, thus producing about 1.2 billion tons of greenhouse gas per year. The textile waste recycling is considered to be of great need and viability in the curricular economy implementation, but it is challenging, especially since these wastes are usually mixed with other fibers. In this way, the present article presents the concept of circular economy related to the textile industry and the ways of recycling fabrics, aiming to reduce environmental impacts. The circular economy presents a model capable of decoupling economic growth from the waste production, transforming waste into new products and materials with maximum efficiency, aiming at reaching an economic model with zero waste, essential to achieve sustainable growth. The transition to a circular economy must begin with the waste prevention and the waste minimization waste deposited in landfills and finally the recycling process implementation. The different recycling processes were shown to be promising wards the significantly contribution to the circular economy. The main recycling technologies, for textile waste, include the hot compression molding process, the mechanical recycling process and the chemical recycling process.